The risk-taking channel of monetary policy in Macedonia: Evidence from credit registry data - Mite Miteski; Ana Mitreska; Mihajlo Vaskov (National Bank of the Republic of Macedonia, 2018)
The last global crisis brought the monetary policy risk-taking channel to the fore, arguing that lingering low interest rates might affect not only the quantity, but the quality of credit extended as well. In line with this debate, this paper is the first effort to empirically investigate the potential existence of the monetary policy risk-taking channel in Macedonia. For this purpose we use a rather unique database of corporate loans, taken from the Credit Registry of the National Bank of the Republic of Macedonia (NBRM), which is complemented with data from banks' balance sheets. By using pooled OLS on semi-annual data for the 2010-2017 period, our study points to an inverse relationship between the policy rate and the ex-ante risk rating assigned by the banks, a finding that is supportive to the existence of the risk-taking channel, although the effect is relatively small. The results prove to be robust after controlling for several bank, loan and time specific variables. We also test for possible difference in the risk-taking by banks conditioned on the capitalization level, but the results do not confirm difference in the reaction. The findings of the study are policy-relevant, as they confirm the need for policy makers to be mindful on financial stability impact when making monetary decisions.
Keywords: E43; E44; E52; G21; 330; Monetary policy; risk taking; ex-ante credit risk; leverage; POLS